Creative professionals and high-skilled agents': Polarization of employment growth? - Jan Wedemeier (European Regional Science Association (ERSA), 2011)
The creative sector is one of the driving forces of total employment growth. Furthermore, economic studies suggest that the clustering of human capital might result in the polarization of economic development. Since the creative sector's de nition is motivated from the insights of the economics of human capital, this e ect might also be relevant to the creative sector. Following these ideas, the objective of the present paper is to analyze the impact of the creative sector on total employment and on creative sector's employment growth in western Germany's regions from 1977 to 2004. For the analysis, the de nitions of the creative sector follow Florida (2002) such as Moeller and Tubadji (2009). However, these approaches focusing on human capital are contrasted with a skill-based approach. It is concluded that the creative sector fosters the regional growth rate of total employment. The results show, moreover, that an initially large share of regional creative professionals pushes further the regional concentration of those professions in agglomerated regions. Driving forces for the concentration are local amenities and knowledge spillovers. These results are as well as con rmed for the high-skilled agents.
Keywords: 330